Baseline fasting plasma insulin levels predict risk for major adverse cardiovascular events among patients with diabetes and high-risk vascular disease: Insights from the ACCELERATE trial. (March 2019) - Kumar, Anirudh; Patel, Divyang R; Wolski, Kathy E; Lincoff, A Michael; Kashyap, Sangeeta R; Ruotolo, Giacomo; McErlean, Ellen; Weerakkody, Govinda; Riesmeyer, Jeffrey S; Nicholls, Stephen J; Nissen, Steven E; Menon, Venu
Background: Despite optimal treatment, type II diabetes mellitus remains associated with an increased risk for future cardiovascular events. We sought to determine the association between baseline fasting plasma insulin levels and major adverse cardiovascular outcomes in patients with type II diabetes mellitus and high-risk vascular disease enrolled in the ACCELERATE (Assessment of Clinical Effects of Cholesteryl Ester Transfer Protein Inhibition with Evacetrapib in Patients at a High Risk for Vascular Outcomes) trial. Methods: We included all patients with type II diabetes mellitus who had a central laboratory measured fasting plasma insulin level drawn at baseline as part of the study protocol. Hazard ratios were generated for the risk of major adverse cardiovascular outcomes (composite of cardiovascular death, non-fatal myocardial infarction, stroke, hospitalization for unstable angina and coronary revascularization) with increasing quartile of baseline fasting plasma insulin level. We then performed a multivariable regression adjusting for significant baseline characteristics. Results: Among 12, 092 patients in ACCELERATE, 2042 patients with type II diabetes mellitus had a baseline fasting plasma insulin level drawn. Median follow-up was 28 months. The study population had a mean age of 66.6 years, 79.2% male and 96.2% had established coronary artery disease. During follow-up, major adverse cardiovascular outcomes occurred in 238 patients (11.6%); of these events, 177 were coronary revascularization (8.7%). We observed a statistically significant relationship between rates of revascularization and rising quartile of baseline fasting plasma insulin level which was not noted for the other individual components of major adverse cardiovascular outcomes. Patients with type II diabetes mellitus who underwent revascularization were noted to have significantly higher baseline fasting plasma insulin levels (27.7 vs 21.4 mU/L, p -value = 0.009) although baseline haemoglobin A1c (6.63% vs 6.55%), body mass index (31.5 vs 31.1 kg/m 2 ) and medical therapy were otherwise similar to the group not undergoing revascularization. Following multivariable regression adjusting for significant characteristics including exposure to evacetrapib, the log of baseline fasting plasma insulin level was found to be an independent predictor for major adverse cardiovascular outcomes (hazard ratio = 1.36, 95% confidence interval = 1.09–1.69, p -value = 0.007); this was driven by need for future revascularization (hazard ratio = 1.56, 95% confidence interval = 1.21–2.00, p -value = 0.001). Conclusion: In a contemporary population of patients with type II diabetes mellitus and high-risk vascular disease on optimum medical therapy, baseline hyperinsulinaemia was an independent predictor for major adverse cardiovascular outcomes and need of future coronary revascularization. These results suggest a pathophysiological link between hyperinsulinaemia and progression of atherosclerotic vascular disease among diabetics.